2019
DOI: 10.3390/polym11121964
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Two-Dimensional MXene and Ammonium Polyphosphate on Enhancing the Fire Safety of Polyvinyl Alcohol Composite Aerogels

Abstract: Fire and smoke suppressions of polyvinyl alcohol (PVA) aerogels are urgently required due to the serious fire hazard they present. MXene, a 2D transition-metal carbide with many excellent properties, is considered a promising synergist for providing excellent flame retardant performance. PVA/ammonium polyphosphate (APP)/transition metal carbide (MXene) composite aerogels were prepared via the freeze-drying method to enhance the flame retardancy. Thermogravimetric analysis, limiting oxygen index, vertical burni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 39 publications
(47 reference statements)
0
32
0
Order By: Relevance
“…[28] They have numerous applications in a variety of fields ranging from energy materials, lubricating additives, nanocomposites, etc. owing to excellent properties; [5,8,13,[28][29][30][31][32][33] MXene-based composites have already been used in many fields such as electromagnetic shielding, [32,34,35] electronics, [36] electrical and thermal conductors, [33,37,38] environmental remediations, [39] supercapacitors, [40,41] fire safety materials, [42] photocatalysts, [43,44] sensors, [10,45] batteries, [46] self-healing composites, [40,47] water purifications, [44,48] antibacterial materials, [49] actuators, [50] and other advanced materials and structures. [8,29,51] For instance, Kang et al [36] developed Ti 3 C 2 MXene reinforced epoxy nanocomposite to enhance thermal and electrical performance wherein they found that the addition of 1.0 wt% few-layer Ti 3 C 2 MXene increases the thermal conductivity to 0.587 W m −1 K −1 , attaining 141.3% improvement compared with that of unreinforced sample.…”
Section: Introductionmentioning
confidence: 99%
“…[28] They have numerous applications in a variety of fields ranging from energy materials, lubricating additives, nanocomposites, etc. owing to excellent properties; [5,8,13,[28][29][30][31][32][33] MXene-based composites have already been used in many fields such as electromagnetic shielding, [32,34,35] electronics, [36] electrical and thermal conductors, [33,37,38] environmental remediations, [39] supercapacitors, [40,41] fire safety materials, [42] photocatalysts, [43,44] sensors, [10,45] batteries, [46] self-healing composites, [40,47] water purifications, [44,48] antibacterial materials, [49] actuators, [50] and other advanced materials and structures. [8,29,51] For instance, Kang et al [36] developed Ti 3 C 2 MXene reinforced epoxy nanocomposite to enhance thermal and electrical performance wherein they found that the addition of 1.0 wt% few-layer Ti 3 C 2 MXene increases the thermal conductivity to 0.587 W m −1 K −1 , attaining 141.3% improvement compared with that of unreinforced sample.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted to increase fire resistance and the effects of combustion and thermal decomposition of polymer composites [ 39 , 40 , 41 , 42 ]. Tang et al [ 39 ] carried out testing on the properties of pure polypropylene (PP) and basalt fiber-reinforced polypropylene (BFRPP) during combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Barczewski et al [ 40 ] indicated that basalt powder can be used as a filler in order to increase the thermal stability and reduce the flammability of polypropylene composites. Sheng et al [ 41 ] described the method of suppressing fire and smoke during the combustion of polyvinyl alcohol (PVA) through the synergistic effect of ammonium polyphosphate (APP), and transition metal carbide (MXene) composite aerogels were prepared via the freeze-drying method. Tests of such materials are usually carried out employing thermogravimetric analysis (TGA) and pyrolysis combustion flow calorimetry (PCFC).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations